Identification of human sperm proteins involved in the interaction with homologous zona pellucida - Lasserre, Andrea (2003)
To identify human sperm proteins involved in homologous zona pellucida (ZP) interaction.Fertilization results from successful interaction between the female and male gametes. Capacitated human spermatozoa initially bind, in a species-specific manner, with the zona pellucida (ZP), an extracellular coat that surrounds all mammalian eggs. As a result of this interaction, spermatozoa undergo an exocytotic process called the acrosome reaction, which allows sperm penetration through the ZP and fusion with the oocyte plasma membrane (1, 2). In many mammals, including humans, it has been shown that the ZP is composed of three glycoproteins, called ZP1, ZP2, and ZP3, which are well characterized at biochemical and molecular level (3, 4). Of the three components, ZP3 is responsible for primary sperm binding to the ZP and induction of the acrosome reaction (AR) (5, 6), while ZP2 would participate in secondary binding to the ZP (7).